Effects of solvents on photonic and fluorescence properties of PtOEP phosphorescent material: Experimental and computational analysis - Gunduz, Bayram; Bulut, Niyazi (Elsevier, 2020)
The effects of different solvents (chloroform, tetrahydrofuran, toluene, methanol, acetone and chlorobenzene) on photonic and fluorescence properties of the PtOEP organic phosphorescent material were investigated with experimental and advanced computational techniques. Many parameters such as angle of incidence/refraction, contrast, optical conductance, electrical conductance, peak absorbance, peak emission, stokes shift, fluorescence quantum yield and sensitivity have been obtained. Theoretical and experimental photonic and fluorescence properties of the PtOEP material for different solvents have been compared. It was found that maximum absorbances for experimental and theoretical calculations arc quite similar at a value of around 389 (nm) and depending on the solvents used here they slightly shifted to larger wavelength. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Organic phosphorescent materials; PtOEP; Theoretical quantum mechanical method; Photonic; Fluorescence quantum yield; Sensitivity